Genetic analysis of neurodevelopmental disorders in children - Wu, Dandan; Li, Rong (Frontiers in Child and Adolescent Psychiatry, 2022)
Purpose To explore the genetic cause of children with unidentified etiology of neurodevelopmental disorders, thus providing references for the diagnosis, treatment and genetic counseling. Design and methods Children with neurodevelopmental disorders but unidentified etiology in the Child Healthcare Department, Children's Hospital of Nanjing Medical University from November 2018 to December 2021 were retrospectively analyzed. A total of 2 ml of peripheral venous blood was collected from the child and their parents for the whole exome sequencing (WES) and copy number variation (CNV) detection. Male children were subjected to fragile X syndrome testing to determine the genetic mutations. For those with positive results, Sanger sequencing was performed to explore the mutations in the gene sites and pedigrees. Results A total of 488 (33.5%) pathogenic variations were detected among 1,457 global developmental/intellectual disabilities (GDD/ID) children, including 362 (24.9%) cases of monogenic mutations, and 111 (7.6%) cases of chromosomal microdeletions or microduplications. There were 15/780 (1.92%) male children with fragile X syndrome. Single point mutations were detected in 277/362 (76.5%) and 85/362 (23.5%) male and female GDD/ID children, respectively, including 295 (81.5%) cases of missense mutations, 32 (8.8%) cases of frameshift mutations, 5 (2.2%) cases of non-sense mutations and 30 (8.3%) cases of splice site mutations. In addition, there were 166 (45.8%) cases of autosomal inheritance and 196 (54.2%) cases of X-linked inheritance. The X chromosome abnormalities were mostly observed in 362 GDD/ID children with monogenic mutations, including 15 cases of the AFF2 gene mutation, 13 cases of the MECP2 gene mutation and 12 cases of the HUWEI gene mutation. The CREBBP gene mutation was the most common autosome abnormality in GDD/ID children with monogenic mutations, which was detected in five cases. There were 74 cases of chromosomal microdeletions, 31 cases of chromosomal microduplications and six cases of both. A total of 114 novel pathogenic mutations responsible for GDD/ID were found, including four novel mutations in MECP2 and TRAPPC9 genes. Conclusion The incidence of genetic abnormalities remains high in NDD children. Abundant novel mutations are responsible for GDD/ID in children, and can be used as references in the diagnosis of neurogenetic diseases.